2005
DOI: 10.1002/jbm.a.30361
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical evaluation of a Zr‐based bulk metallic glass in a phosphate‐buffered saline electrolyte

Abstract: Bulk metallic glasses (BMGs) represent an emerging class of materials with an amorphous structure and a unique combination of properties. The objectives of this investigation were to define the electrochemical behavior of a specific Zr-based BMG alloy in a physiologically relevant environment and to compare these properties to standard, crystalline biomaterials as well as other Zr-based BMG compositions. Cyclic-anodic-polarization studies were conducted with a Zr52.5Cu17.9Ni14.6Al10.0Ti5.0 (at %) BMG in a phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 40 publications
0
55
2
Order By: Relevance
“…For example, Pd-Cu-Ni-P metallic glasses were used as die materials while Zr-based metallic glasses were used for sporting equipments. In addition, the metallic glasses have also been proposed for some biomedical applications [2,3]. For example, it can be used for making bone fracture fixation and hip arthroplasty components where a low modulus comparable to bone is critical to avoid stress shielding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pd-Cu-Ni-P metallic glasses were used as die materials while Zr-based metallic glasses were used for sporting equipments. In addition, the metallic glasses have also been proposed for some biomedical applications [2,3]. For example, it can be used for making bone fracture fixation and hip arthroplasty components where a low modulus comparable to bone is critical to avoid stress shielding.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can be used for making bone fracture fixation and hip arthroplasty components where a low modulus comparable to bone is critical to avoid stress shielding. Furthermore, the superior strength would permit a smaller, less intrusive device that would be capable of withstanding the large forces generated within the skeletal system of the human body [2]. However, the applications of the metallic glasses require high chemical stability in various environments in order to ensure its lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,7-9,13-33) Favorable BMG properties are: high strength, fracture toughness, wear and corrosion resistance; 1,8,9,14,[16][17][18][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] low modulus, magnetic energy loss, etc. ; good impact toughness, formability, and fatigue limits; high hardness, ductility in compression, etc.. 1,[16][17][18]20,34,35) Improved BMG properties are due to a lack of grain boundaries, microstructures, long-range order, etc., and inherent structural and chemical homogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…Hiromoto et al [4][5][6] studied the effect of chloride-ion concentration, PH value, surface finishing and dissolved oxygen pressure on the polarization behavior of Zr 65 Cu 17:5 Ni 10 Al 7:5 metallic glass in phosphate buffered solution (PBS), and found that the glassy alloy exhibits a similar polarization resistance to pure titanium. On the other hand, Morrison et al 7,8) carried out a cyclic-anodicpolarization study on Zr 41:2 Ti 13:8 Ni 10 Cu 12:5 Be 22:5 BMG (Vit.1) in PBS solution, and revealed that Vit. 1 has a much lower corrosion penetration rate than 316 L stainless steal, but an equivalent value to Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%